Metronomic Chemotherapy in Dogs and Cats: Mechanisms, Indications, and Clinical Perspectives - Bitencourt, Rafael Costa [UNESP]; Cruvinel, Giovanna Gabrielle [UNESP]; de Castro Terrabuio, Verônica Maria Teixeira [UNESP]; Linhares, Laís Calazans Menescal [UNESP]; Bispo, Guilherme Andraus [UNESP]; Anai, Letícia Abrahão [UNESP]; da Rosa Sobreira, Márcia Ferreira [UNESP]; Camplesi, Annelise Carla [UNESP]; De Nardi, Andrigo Barboza [UNESP]; Santana, Aureo Evangelista [UNESP] (MDPI, 2025)
Metronomic chemotherapy (MC) represents an emerging strategy in veterinary oncology which involves the continuous or regularly scheduled administration of low-dose chemotherapeutic agents. Unlike conventional protocols known as maximum tolerated dose chemotherapy (MTDC), MC aims to inhibit tumor angiogenesis, stimulate antitumor immune responses, and delay or prevent the emergence of drug resistance. This review is structured into three key sections: the mechanisms of action of MC; its clinical indications in dogs and cats, particularly for advanced or treatment-resistant cancers; and reported outcomes regarding efficacy, safety, and tolerability. Additionally, we explore the growing interest in combining MC with other therapies, as well as the challenges and future directions for optimizing its use. Current evidence suggests that MC is a promising and well-tolerated option for managing various malignancies-such as carcinomas, sarcomas, and hemangiosarcomas-especially in patients who are not candidates for MTDC.